Effects of Industrial Waste Effluent on Soil Microflora and Rice Plants - U. Suriawiria (Journal of Mathematical and Fundamental Sciences, 1979)
Abstract. Industrial waste effluents, particularly from chemical industries, causes pollution. Like other chemical industries, the Letjes Paper Mill (Probolinggo), produce approximately 800 cubic meters of waste effluents per hour, which is directly discharge into the immediate surroundings without any treatment beforehand. The present study was, therefore, undertaken to determine the effects of continous dischargal of the Letjes Paper Mill waste effluents on soil microflora and rice plants. Sari. Buangan industry, terutama dari industri kimia, merupakan penyebab pencemaran. Seperti pula industry kimia lainnya, Pabrik Kertas Letjes (Probolinggo), menghasilkan lebih kurang 800 meter-kubik air-buangan setiap jamnya, yang langsung dibuang ke lingkungannya tanpa pengolahan terlebih dahulu. Penelitian ini dimaksudkan untuk mengetahui efek dari air bunangan Pabrik Kertas Letjes yang dibuang terus-menerus, terhadap mikroflora tanah dan tanaman padi.